The potential occurrence of Puccinia asparagi in New Zealand - Viljanen-Rollinson, S.L.H.; Deng, Y.; Marroni, M.V.; Cheah, L-H (New Zealand Plant Protection, 2006)
Wind dispersal of plant pathogens is one of the pathways of entry for rust fungi into New Zealand from Australia Asparagus rust (caused by Puccinia asparagi) has already caused damage to asparagus crops in Australia It poses a serious risk to New Zealands biosecurity and the 2000 ha asparagus industry CLIMEX Match Climates simulations showed that climates in locations where asparagus rust is already present are similar to New Zealand climates